Wanita Dewasa Muda dengan Gagal Jantung, Pneumonia, dan Hipoksemia: Komplikasi Obesitas Morbid – Laporan Kasus: Laporan Kasus - Kristianus, David; Ngantung, Robert Noldy; Sutanto, Hari (Cermin Dunia Kedokteran, 2026)
Introduction: Heart failure is a clinical syndrome resulting from structural or functional abnormalities of the heart that cause cardinal symptoms and signs of heart failure. One of the contributing factors to increased incidence of heart failure among young people is obesity. Obesity also increases the risk of impaired lung function and other organs. Case: A 25-year-old female with shortness of breath since 1 day. Peripheral oxygen saturation (SpO2) was 80% in room air. Her body mass index was 52 kg/m2. Chest radiology showed cardiomegaly with pulmonary infiltrates and edema. Echocardiography revealed a left ventricular ejection fraction of 79.8% and mild left ventricular diastolic dysfunction. Discussion: Diagnosis was heart failure with preserved ejection fraction (HFpEF) 79.8% and pneumonia. Treatment with furosemide and antibiotics relieved the shortness of breath, congestion, and pulmonary infiltrates, yet the patient continued to experience hypoxemia in room air. Chest physiotherapy and breathing exercises were applied to improve the impaired lung function due to obesity. Conclusion: Obesity is a risk factor for heart failure in young adult population. Maintaining ideal body weight is important to prevent obesity and its complications.